Expressions of Olfactory Proteins in Locust Olfactory Organs and a Palp Odorant Receptor Involved in Plant Aldehydes Detection - Li, Hongwei; Wang, Peng; Zhang, Liwei; Xu, Xiao; Cao, Zewen; Zhang, Long (Frontiers in Physiology, 2018)
The main chemosensory organs of locusts are consisted of the antennae and the mouthparts (maxillary and labial palps), which are suggested to perform different functions. However, little is known about the differences of these two organs at molecular level. To understand the differences of locust antennae and palps in olfaction, the electrophysiological response and olfactory gene expression of these two organs were conducted. Our electrophysiological experiments with Locusta migratoria showed that the responses of mouthpart palps and antennae to odorants are quite different. Only a few odorants, such as (E,E)-2,4-hexadienal and (E,E)-2,4-heptadienal, elicited stronger electrophysiological responses of both maxillary and labial palps in comparison to the antennae. Additionally, we obtained 114 and 11 putative odorant receptor (OR) gene segments from the antennal and palp transcriptomes, respectively. Two novel odorant-binding proteins (OBPs; OBP15 and OBP16) and one novel OR (OR142) were identified for the first time. Out of the 16 OBP genes tested in RT-PCR and qPCR analyses, OBP8 was highly expressed in the nymphal palps. OBP4, OBP10, and OBP16 were only detected in the antennae. The other 11 OBP genes were jointly expressed in both antennae and palps. The relative expression level of OBP6 in male palps was much higher than that in female palps. Furthermore, for the 11 OR genes identified in palp transcriptome, the expression levels of OR12, OR13, OR14, and OR18 in the palps were significantly higher than those in the antennae. OR12 in palps was demonstrated to be involved in detection of hexanal and E-2-hexenal, as well as (E,E)-2,4-heptadienal. Our results provide information on the different olfactory roles of locust antennae and palps at the molecular level.